The importance of knowing other players' parts when playing in a chamber group / Zulfikri Arief Shaimai - Shaimai, Zulfikri Arief (Faculty of Music, 2017)
This study was carried out in February-July 2016 at the Faculty of Music UiTM Shah Alam. This study focused on the Importance of Knowing Other Players' Parts When Playing in an Ensemble. This study is based on responses from respondents regarding the importance of knowing other players' parts. The main objectives of this study are to find out how musicians learn other players' parts, to investigate the importance of knowing other players' parts and to identify the outcome of learning other players' parts when playing in a chamber group. This study concludes that it is essential to know other players' parts when playing in an ensemble. There are also a lot of information regarding the ways of learning other players' parts and its advantages towards the ensemble that can be used as a guideline to students who are interested in playing chamber music.